2013
DOI: 10.1136/annrheumdis-2013-204128
|View full text |Cite
|
Sign up to set email alerts
|

Drug survival on TNF inhibitors in patients with rheumatoid arthritis comparison of adalimumab, etanercept and infliximab

Abstract: ObjectiveTo compare drug survival on adalimumab, etanercept and infliximab in patients with rheumatoid arthritis (RA).MethodsPatients with RA (n=9139; 76% women; mean age 56 years) starting their first tumour necrosis factor (TNF) inhibitor between 2003 and 2011 were identified in the Swedish Biologics Register (ARTIS). Data were collected through 31 December 2011. Drug survival over up to 5 years of follow-up was compared overall and by period of treatment start (2003–2005/2006–2009; n=3168/4184) with adjustm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
110
6
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(139 citation statements)
references
References 27 publications
16
110
6
2
Order By: Relevance
“…8,9 More recently, literature about the drug survival of patients with psoriasis treated with biologics has been published. 10,11 To the best of our knowledge, this is the first study on drug survival in patients with AD treated with CsA in daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 More recently, literature about the drug survival of patients with psoriasis treated with biologics has been published. 10,11 To the best of our knowledge, this is the first study on drug survival in patients with AD treated with CsA in daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…Drug survival time is a composite measure, integrating, among other things, both efficacy and tolerance to therapy. Drug survival has been used in several studies and has been shown to be a clinically relevant measurement for long‐term drug efficacy 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…The relative efficacy of these agents in various conditions are still not clear as there are no randomized controlled trials to date that compared the clinical efficacy or safety head-to-head of these five agents in any one inflammatory condition (PubMed search, January 17, 2015). However, there are studies that compared two of these drugs or compared one of these drugs with non-biologic, conventional DMARDs (Kievit et al 2007;Neovius et al 2015;Rau 2010). There are also several meta-analysis studies that indirectly compared the efficacy and safety of these five agents in the treatment of rheumatoid arthritis (Aaltonen et al 2012;Behrens et al 2014;Michaud et al 2014;Machado et al 2013).…”
Section: Comparative Efficacy and Safetymentioning
confidence: 98%